The Yang-Laplace Transform for Solving the IVPs with Local Fractional Derivative - Chun-Guang Zhao; Ai-Min Yang; Hossein Jafari; Ahmad Haghbin (Abstract and Applied Analysis)
The IVPs with local fractional derivative are considered in this paper. Analytical solutions for the homogeneous and nonhomogeneous local fractional differential equations are discussed by using the Yang-Laplace transform.